2018
DOI: 10.1123/ijspp.2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Is the Functional Threshold Power a Valid Surrogate of the Lactate Threshold?

Abstract: FTP is a valid field test-based marker for the assessment of endurance fitness. However, caution should be taken when using FTP interchangeably with LT, as the bias between markers seems to depend on the athlete's fitness status. Whereas FTP provides a good estimate of LT in trained cyclists, in recreational cyclists, it may underestimate LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 32 publications
5
48
1
Order By: Relevance
“…In accordance with the t lim observed in the present study, a strong agreement between RCP and the mean PO during a 20-min test has been previously reported [ 22 ]. Our group recently demonstrated a good agreement between the FTP and the lactate threshold determined with the ‘D-max’ method [ 23 ]. The D-max has also been reported to have a strong correlation ( r = 0.97) with the MLSS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the t lim observed in the present study, a strong agreement between RCP and the mean PO during a 20-min test has been previously reported [ 22 ]. Our group recently demonstrated a good agreement between the FTP and the lactate threshold determined with the ‘D-max’ method [ 23 ]. The D-max has also been reported to have a strong correlation ( r = 0.97) with the MLSS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is pertinent as many regard MLSS to be the criterion measure for tolerable exercise 2 . Furthermore, although cross-sectional comparisons between FTP95% and other markers of performance have been made [5][6][7]9 , no study has evaluated the ability or sensitivity of the FTP95% test to track changes in fitness level on a longitudinal basis.…”
Section: Introductionmentioning
confidence: 99%
“…It is also the key metric in a series of calculations of training load and exercise intensity (i.e., training stress score [TSS], intensity factor [IF]) [6]. Moreover, FTP is used as an indirect and practical estimate of the anaerobic threshold (AnT) and maximal lactate steady state (MLSS) [7][8][9]. Due to the long test duration (i.e., 60 min), it was suggested that the FTP might be determined as 95 % of the mean PO in a 20-min TT (FTP 20 ) [6].…”
Section: Introductionmentioning
confidence: 99%
“…A recent concern in sports sciences is the applicability of the tests developed for athletes in the "real world" [20]. Recent studies [7][8][9] have investigated the validity of the FTP 20 test with AnT, MLSS, and FTP 60 . Overall, trivial differences (bias) were found between FTP 20 (original warm-up) with FTP 60 , AnT, and MLSS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation